Description of the day of judgement and the Prophet’s intercession in Malay manuscripts: al-Raniri’s Akhbar Akhira and related texts - Shiozaki, Hiroko (2015)
This paper aims to compare Jawi kitabs that have descriptions about the matters of hereafter in order to find out the varieties and relationships among the kitabs. For this purpose, the presenter analyzes manuscripts of Akhbar Akhirah wa Ahwal al-Kiyamah written by al-Raniri as the main text and compare the description of the day of judgement with some other major kitabs distributed in the Southeast Asia on the same topic, such as Daqaiq al-Akhbar (both Arabic version by Abd al-Rahim al-Qadhi and Malay version by Ahmad bin Muhammad Yunus Lingga), Kashf al-Ghaibiyah by Zainul Abidin bin Muhammad al-Fathani and Khabarol Akhirah in Maranao (partially translated in [Kawashima 2015]) with reference to other major kitabs from the Middle East, such as “the Book of the Rememberance of Death” from al-Ghazali’s Ihya Ulum ad-Din and al-Qurtubi’s al-Tadhkirah. The first part of this paper discusses the variations of the sequence of the matters on the day of judgement that is found in above mentioned books. The selection of topics and their explanation can be categorized into some types from certain perspectives. For example, the way to begin the story of hereafter with the explanation of the creation of the world (that begins with the creation of the Light of Muhammad) is common for Akhbar Akhirah, Daqaiq, Kashf and Khabarol Akhirah but not shared by other books mentioned above. The second part of this paper focuses on the explanation of the concept of intercession (shafaa) among various matters of the day of judgement, to compare the characteristics of the above-mentioned kitabs from another perspective. The explanation of the intercession by the Prophet Muhammad, that is to be done upon the request from the people of the concourse, is almost the same in all books based on similar hadiths. However, a great variety is found in the explanation of the intercession by the Prophet and other people that is to rescue the believers from the hell. For example, while al-Ghazali explains the intercession by ulama and other pious people under the topic of intercession, Akhbar Akhirah mentions the process of salvation from the hell in different context without using the concept of “intercession”.